Geschichte lernen im digitalen Wandel Learning History in a Transforming Digital World: A Book Project Subjected to Open Peer Review - Demantowsky, Marko (De Gruyter, 2014)
Young people communicate through social networks, and seek information and opinion online. They participate publicly in real-time social debates. These radical changes in their life worlds have implications for their views of history and for the collective historical culture. Thus, historical instruction is facing entirely new challenges. The contributors to this volume submitted to an open review process prior to publication.